IMPROVEMENT OF MATHEMATICS LEARNING OUTCOMES MATERIAL ON FLAT WAKE THROUGH IMAGE MEDIA IN GRADE IV STUDENTS OF SD NEGERI 21 PULAU PUNJUNG FOR THE 2019/2020 ACADEMIC YEAR - Umi Putri Yanti (JURNAL EDUSCIENCE, 2023)
This research was motivated by a lack of motivation in learning mathematics in grade IV A SDN 21 Pulau Punjung. This research was conducted to increase student learning motivation in mathematics by using image media in class IV A SDN 21 Pulau Punjung. The method used is class action research conducted by planning, enforcement, and reflection. The analysis uses a picture of student learning outcomes seen from the absorbency and completeness of student learning described descriptively. The results showed an increase in mathematics learning outcomes through image media, as seen in the average student activity from cycle I reaching 51.01%, and experienced an increase in cycle II, reaching 54.5% to 83%. The increase is also found in students' learning absorption starting from procyclical, reaching 51.36% increased to 80.9% in cycle III.Keywords: learning outcome, math.AbstrakPenellitian ini dilatarbelakangi oleh kurangnya motivasi dalam pembelajaran matematika di kelas IV A SDN 21 Pulau Punjung. Penelitian ini dilakukan dalam peningkatan motivasi belajar siswa pada mata pelajaran Matematika dengan menggunakan media gambar di kelas IV A SDN 21 Pulau Punjung. Metode yang digunakan adalah penelitian tindakan kelas yang dilakukan dengan perencanaan, penindakan, dan refleksi. Analisis menggunakan gambaran hasil belajar siswa yang dilihat dari daya serap, ketuntasan pembelajaran siswa yang dijabarkan secara desktiptif. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil pembelajaran matematika melaui penggunaan media gambar tampak pada rerata aktivitas siswa dari siklus I mencapai 51,01% mengalami peningkatan pada siklus II mencapai 54,5 % meningkat menjadi 83% pada . peningkatan juga terdapat pada daya serap siswa dalam pembelajaran dimulai dari prasiklus mencapai 51,36% meningkat menjadi 80,9% pada siklus III.Kata Kunci: hasil belajar, matematika, media gambar